بنية الإيقاع العروضي في شعر حسين زيدان - أقطي, نوال (جامعة الوادي - university of Eloued, 2021)
يرنو هذا البحث إلى دراسة بنية الإيقاع العروضي في شعر حسين زيدان، لاسيما أن خطابه الشعري يتميز بتباين الأنساق العروضية واختلافها، فهو يستند إلى ظواهر عروضية عدة (التداخل والتنوع والتناوب والتدوير). ويستعين بالمنهجين الوصفي والإحصائي للكشف عن الأوزان المهيمنة، وتحديد قيم الزحافات فيها، ثم يشير إلى أثرها الجمالي، ويعمل على تحليل أهم التقنيات العروضية المستخدمة. This research aims at studying the structure of the rhythm metric in the poetry of Hussein Zaidan, especially since his poetic speech is characterized by the variations and differences of the metric patterns. It is based on several metric phenomena (interference, diversity, alternation and rotation). The research, at hand, uses the descriptive and statistical approaches to investigate the dominant measures and to determine the values of the deviations in them, and then indicates their aesthetic impact. It works on analyzing the most important metric techniques used.
مقال
Keywords: النسق العروضي المهيمن؛ التداخل؛ التنوع؛ التناوب؛التدوير.